1997
DOI: 10.1111/j.1439-0434.1997.tb00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Of Barley Yellow Dwarf Virus and Fusarium culmorum (W. G. Sm.) Sacc. in Winter Wheat

Abstract: The barley yellow dwarf viras (BYDV) epidetnics, which occtirred predomitiantly in northern Gemiany in 1988-90 and caused untisual yield losses of wheat, prompted our study on interactions of BYDV and Fusarium eulmorum. At the late stages of plant development (EC 55/65) infections with BYDV resulted in a lower yield reduction of wheat plants than infections with F. culmorum. Combined infections at flowering resulted in severer yield reduction, indicating additive effects of the two pathogens. However, if wheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The results suggest that BYDV infections affect grain yield of wheat cultivars to different extents and wheat cultivars may react differently with interactions between BYD-disease and FHB. Koch and Huth (1997) reported that double infections of winter wheat cultivars Orestis and Kraka with BYDV and F. culmorum had significantly greater effects on the yield of wheat plants than single infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggest that BYDV infections affect grain yield of wheat cultivars to different extents and wheat cultivars may react differently with interactions between BYD-disease and FHB. Koch and Huth (1997) reported that double infections of winter wheat cultivars Orestis and Kraka with BYDV and F. culmorum had significantly greater effects on the yield of wheat plants than single infections.…”
Section: Discussionmentioning
confidence: 99%
“…Study of effects of BYDV infection in oats and durum wheat on the development of root rot disease caused by Cochliobolus sativus showed that plants diseased by both pathogens were more severely affected than plants infected by each pathogen alone (Scott, 1968). Koch and Huth (1997) concluded that susceptibility of wheat plants to F. culmorum would be increased in epidemic years of BYDV.…”
Section: Introductionmentioning
confidence: 99%
“…Infection with BYDV‐PAV induces a reduction of root length and of the number of root shoots correlated with a reduction of tiller growth (Hoffman & Kolb, 1997). Damage depends on abiotic and biotic conditions and BYDD can increase susceptibility to frost, drought, and diseases like rusts, snow mould ( Microdochium nivale ) (Collin et al ., 1997) and fusarium ear blight (Koch & Huth, 1997; Liu & Buchenauer, 2005). Yield losses under conditions favourable to epidemics ranged from 5 to 80%, with an average of 30% (Lister & Ranieri, 1995; Perry et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Fusarium culmorum present itself as a weak pathogen and infects roots more passively with assistance of nematode or wound. Fusarium culmorum may intensify its disease impact through association with other diseases (Koch & Huth, 1997). The absence of microconidia in F. culmorum limits the quantity of propagules or innocula produced for infection.…”
Section: Diversity Of Fusarium Species and Frequency Of Distribution ...mentioning
confidence: 99%